Analisis Wacana Kritis Kasus Penyerangan Terhadap Jemaah Ahmadiyah di Cikeusik - Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2018)
This paper examines the phenomenon of Ahmadiyah congregation in Indonesia which has long been a conversation for many years. The phenomenon of Ahmadiyah congregation raised in this paper is the result of news from Kompas Online media, in case of attack in Cikeusik in 2011 ago. The method used is critical discourse analysis from Theo Van Leeuwen, who sees the representation of social actors and activities displayed in a text. The representation of the actor and the social act is shown through exclusion and inclusion. The main news that became the object of analysis is the news published by Kompas Online on February 06, 2011, entitled